Conflict in the profit-led growth model - Romar Correa (Economics: The Open-Access, Open-Assessment E-Journal, 2015)
We model the interaction between capitalists and entrepreneurs as a dynamic game. The open-loop Nash equilibrium and the closed-loop Nash equilibrium are distinguished. The purpose is to answer some questions that have arisen in the development of profit-led versus wage-led growth models. We find that the rate of profit and the discount rate as well as the responsiveness of the wage rate or aggregate consumption to the accumulation of capital are critical to explaining the change in regimes.
Keywords: B51; C73; 330; capital accumulation; rentier consumption